2022
DOI: 10.1155/2022/5642406
|View full text |Cite
|
Sign up to set email alerts
|

Combination of White Blood Cell Count to Mean Platelet Volume Ratio and Neutrophil-to-Platelet Ratio Predicts Long-Term Adverse Events in Patients with MINOCA

Abstract: Background. White blood cell count to mean platelet volume ratio (WMR) and neutrophil-to-platelet ratio (NPR) have been demonstrated as prognostic inflammatory biomarkers of the acute coronary syndrome. We aimed to evaluate the prognostic value of WMR and NPR among myocardial infarction with nonobstructive coronary arteries (MINOCA) patients. Method. A total of 274 MINOCA patients were enrolled. Baseline clinical data, blood cell panel, and biochemical parameters were evaluated. The patients were classified ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…White blood cell count to mean platelet-volume ratio (WMR) and neutrophil-to-platelet ratio (NPR) are inflammatory biomarkers that have been shown to predict clinical outcomes in patients presenting with acute MI. Mohammed et al's study revealed that this correlation is also present in MINOCA, and patients with high WMR and NPR were at increased risk of MACE [ 11 ]. They are pointing to the possible use of these ratios as risk prediction markers in the clinical assessment of MINOCA patients.…”
Section: Reviewmentioning
confidence: 99%

MINOCA: A Working Diagnosis

Rodríguez Candelario,
Perez-Aybar,
Roman-Ramos
2023
Cureus
“…White blood cell count to mean platelet-volume ratio (WMR) and neutrophil-to-platelet ratio (NPR) are inflammatory biomarkers that have been shown to predict clinical outcomes in patients presenting with acute MI. Mohammed et al's study revealed that this correlation is also present in MINOCA, and patients with high WMR and NPR were at increased risk of MACE [ 11 ]. They are pointing to the possible use of these ratios as risk prediction markers in the clinical assessment of MINOCA patients.…”
Section: Reviewmentioning
confidence: 99%

MINOCA: A Working Diagnosis

Rodríguez Candelario,
Perez-Aybar,
Roman-Ramos
2023
Cureus
“…Another indicator of systemic inflammation is the neutrophil/lymphocyte ratio, established as an indicator of strong systemic inflammation associated with mortality and adverse cardiac events, a study that analyzed the combination of high neutrophil/lymphocyte ratio and high mean platelet volume concluded that it independently predicts major adverse cardiovascular events in patients with coronary syndrome ( 13 ). Thus, both MPV and NLR can be used as biomarkers of inflammation as predictors of adverse arterial events due to atheroma plaque formation ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other in ammatory markers of myocardial injury include the following: A high white blood cell count to mean platelet volume ratio and neutrophil-to-platelet ratio, separately or in combination, have been associated with an increased risk of major adverse cardiovascular events in patients [7]. Moreover, the peak level of C-reactive protein (CRP) can serve as a predictive marker for transmural MI, and its predictive ability is comparable to that of peak creatine kinase-Myocardial Band (CK-MB) and highsensitivity cardiac troponin T levels [8].…”
Section: Introductionmentioning
confidence: 99%